Unsur Eksternal Wacana pada Film Bertemakan Wabah Virus - Siti Rukiyah; Mardiana Sari; Yenny Puspita (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of this study was to obtain a deep understanding of the external elements of discourse in the virus outbreak themed film. The film with the theme of the virus outbreak which was used as the object of research was entitled Contagion. This qualitative descriptive research uses discourse analysis method with qualitative content analysis. Collecting data using documentation techniques through literature study. The steps used in analyzing the external elements of discourse in the virus epidemic-themed film are as follows: 1) watching the film entitled The Contagion carefully and repeatedly in order to understand its content and meaning, then making a synopsis of the film, 2) recording quotations - text quotes, 3) analyzing the external elements of discourse in the citation of the film text, 4) discussing and interpreting the research results obtained, 5) formulating and drawing conclusions, and 6) compiling research reports. The validity of research data by means of member checks, accuracy, and adequacy of theories related to the object of research. The results show that the external elements that build discourse in the film The Contagion, which have 12 implicatures with details of 11 data are conversational implicatures or it can be said that conventional implicatures and 1 non-conventional implicature data, namely implications that must draw conclusions based on certain phenomena or situations, then there are 5 presupposition data are included in the factive type, 1 existential data, 5 counterfactual data and 2 non-factive data, then in the context 9 physical context data and 4 socio-psychological context data are found.